Multicentre analysis of seizure outcome predicted by removal of high-frequency oscillations - Dimakopoulos, Vasileios; Gotman, Jean; Klimes, Petr; von Ellenrieder, Nicolas; Tan, Shi Bei; Smith, Garnett; Gliske, Stephen V; Maltseva, Margarita; Manalo, Minette Krisel; Pail, Martin; Brazdil, Milan; van Blooijs, Dorien; et al. (Brain, 2025)
In drug-resistant focal epilepsy, planning surgical resection can involve presurgical intracranial EEG (iEEG) recordings to detect seizures and other iEEG patterns to improve postsurgical seizure outcome. We hypothesized that resection of tissue generating interictal high-frequency oscillations (HFOs, 80-500 Hz) in the iEEG predicts surgical outcome. In eight international epilepsy centres, iEEG was recorded during the presurgical evaluation of patients. The patients were of all ages, had epilepsy of all types, and underwent surgical resection of a single focus aiming at seizure freedom. In a prospective analysis, we applied a fully automated definition of HFO that was independent of the dataset. Using an observational cohort design that was blinded to postsurgical seizure outcome, we analysed HFO rates during non-rapid-eye-movement sleep. If channels had consistently high rates over multiple epochs, they were labelled the 'HFO area'. After HFO analysis, centres provided the electrode contacts located in the resected volume and the seizure outcome at follow-up ≥24 months after surgery. The study was registered at www.clinicaltrials.gov (NCT05332990). We received 160 iEEG datasets. In 146 datasets (91%), the HFO area could be defined. The patients with a completely resected HFO area were more likely to achieve seizure freedom in comparison to those without [odds ratio 2.61, 95% confidence interval (CI) 1.15-5.91, P = 0.02]. Among seizure-free patients, the HFO area was completely resected in 31 and not completely resected in 43. Among patients with recurrent seizures, the HFO area was completely resected in 14 and not completely resected in 58. When predicting seizure freedom, the negative predictive value of the HFO area (68%, CI 52-81) was higher than that for the resected volume as a predictor by itself (51%, CI 42-59, P = 4 × 10-5). The sensitivity and specificity for complete HFO area resection were 0.88 (CI 0.72-0.98) and 0.39 (CI 0.25-0.54), respectively, and the area under the curve was 0.83 (CI 0.58-0.97), indicating good predictive performance. In a blinded cohort study from independent epilepsy centres, applying a previously validated algorithm for HFO marking without the need for adjusting to new datasets allowed us to validate the clinical relevance of HFOs to plan the surgical resection.
Keywords: Female; lidé středního věku; elektrokortikografie; Electroencephalography; Adolescent; mužské pohlaví; mladý dospělý; prospektivní studie; Humans; dospělí; elektroencefalografie; Prospective Studies; Electrocorticography; Seizures; lidé; Middle Aged; záchvaty; Treatment Outcome; ženské pohlaví; Child; refrakterní epilepsie; Young Adult; dítě; Adult; Drug Resistant Epilepsy; Male; mladiství; výsledek terapie